Description of Drugs Abuse in Student Urine at One of the Vocational High Schools in Yogyakarta - Dian Wuri Astuti; Tiara Kurniati; Vikki Indriani; Siti Fatimah; Titah Dewi Rahadian (Universitas Muhammadiyah Palu, 2024)
Yogyakarta Special Region (DIY) has become one of the target markets for narcotics and illegal drugs. The DIY Provincial National Narcotics Agency (BNNP) in 2021 stated that the Indonesian population aged 15-64 years had been exposed to using drugs. Referring to data from BNNP DIY ranks 5th in drug abuse cases and the most teenagers. DIY has a potential that is quite vulnerable considering the number of teenagers who continue their education in the city of Yogyakarta. The purpose of this study was to determine the presence or absence of amphetamine and methamphetamine in one of the vocational high schools students in DIY. This type of research is descriptive research. Amphetamine and methamphetamine examination using a competitive immunochromatographic method. The sample used was the urine of students as many as 27 samples. The data analysis of the research results was carried out descriptively and presented in the form of tables and narratives. In this study, no urine samples containing amphetamine and methamphetamine were found, red lines appeared on Control (C) and Test (T). There were no positive results containing amphetamine and methamphetamine from 27 (100%) samples examined.